Autism Spectrum Disorder (ASD) Law in Chile - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2024)
The TEA Law ensures the right to equal opportunities and safeguards the social inclusion of children, adolescents and adults with ASD, eliminating any form of discrimination. It promotes a comprehensive approach in the social, health and education areas, and raises awareness in society on this issue. The law is based on fundamental principles such as dignified treatment, progressive autonomy, gender perspective, intersectorality, participation and social dialogue, early detection, continuous monitoring, and neurodiversity.